Chromatic discrimination measures in mature observers depend on the response window - Fars, Julien; Fernandes, Thiago P.; Huchzermeyer, Cord; Kremers, Jan; Paramei, Galina V. (Scientific Reports, 2022)
Our past anecdotal evidence prompted that a longer response window (RW) in the Trivector test (Cambridge Colour Test) improved mature observers' estimates of chromatic discrimination. Here, we systematically explored whether RW variation affects chromatic discrimination thresholds measured by the length of Protan, Deutan and Tritan vectors. We employed the Trivector test with three RWs: 3 s, 5 s, and 8 s. Data of 30 healthy normal trichromats were stratified as age groups: 'young' (20-29 years), 'middle-aged' (31-48 years), and 'mature' (57-64 years). We found that for the 'young' and 'middle-aged', the thresholds were comparable at all tested RWs. However, the RW effect was apparent for the 'mature' observers: their Protan and Tritan thresholds decreased at 8-s RW compared to 3-s RW; moreover, their Tritan threshold decreased at 5-s RW compared to 3-s RW. Elevated discrimination thresholds at shorter RWs imply that for accurate performance, older observers require longer stimulus exposure and are indicative of ageing effects manifested by an increase in critical processing duration. Acknowledging low numbers in our 'middle-aged' and 'mature' samples, we consider our study as pilot. Nonetheless, our findings encourage us to advocate a RW extension in the Trivector protocol for testing mature observers, to ensure veridical measures of their chromatic discrimination by disentangling these from other ageing effects-slowing down of both motor responses and visual processing.
CRIS-Team WoS Importer:2022-06-17

Chromatic discrimination: The response window does matter for veridical measurement in mature observers - Fars, Julien; Fernandes, Thiago M. P.; Huchzermeyer, Cord; Kremers, Jan; Paramei, Galina V. (PERCEPTION, 2021)
CRIS-Team WoS Importer:2022-01-21

Complementarity of sensitivity and just noticeable difference in the study of Retinitis Pigmentosa and Stargardt disease - Fars, Julien; Kremers, Jan; Huchzermeyer, Cord (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Discriminating anomalous trichromacy and cone degeneration in retinitis pigmentosa patients - Fars, Julien; Kremers, Jan; Huchzermeyer, Cord (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Neue Techniken zur Quantifizierung des Farbsinns bei Störungen der Zapfenfunktion - Huchzermeyer, Cord; Fars, Julien; Stöhr, Heidi; Kremers, Jan (Ophthalmologe, 2020)
Background: Inherited retinal diseases with cone dysfunction can be accompanied by severe visual loss and a marked loss of color vision despite relatively normal fundus appearance. Autosomal dominant occult macular dystrophy (RP1L1 gene) and X‑chromosomal retinitis pigmentosa (RPGR gene, including heterozygous female carriers) are important examples. New examination techniques enable quantification of the extent of color vision disturbances. Methods: After a thorough clinical examination, color discrimination and cone function were quantified. The Cambridge color test is a computer-based test that generates pseudo-isochromatic plates with Landolt C figures for quantifying color discrimination along several axes in color space. Examination of photorecepor-specific temporal contrast sensitivity is performed by subtle cyclic modulation of the spectral composition of a light stimulus. Molecular diagnostics were carried out by next generation sequencing (NGS)-based targeted gene panel analysis and Sanger sequencing. Results: Markedly reduced color discrimination as well as reduced photoreceptor-specific temporal contrast sensitivity could be demonstrated in two patients with occult macular dystrophy and two heterozygous female carriers of RPGR mutations. Conclusion: The demonstration of dyschromatopsia is very helpful in the diagnosis of inherited retinal diseases, in addition to modern imaging techniques, such as optical coherence tomography (OCT) and fundus fluorescence. New functional techniques enable quantification of color vision disturbances and could be useful as outcome parameters in clinical trials of new gene and stem cell-based therapies.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Color vision; Cone dystrophy; Contrast sensitivity; Photoreceptors; Retinitis pigmentosa

Patterns of photoreceptor-specific temporal contrast sensitivity losses in patients with different phenotypic variants of retinitis pigmentosa - Huchzermeyer, Cord; Fars, Julien; Lorenz, Birgit; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Perifoveal cone- And rod-mediated temporal contrast sensitivities in stargardt disease/fundus flavimaculatus - Fars, Julien; Pasutto, Francesca; Kremers, Jan; Huchzermeyer, Cord (Investigative Ophthalmology & Visual Science, 2021)
PURPOSE. The purpose of this study was to compare L-cone–driven, S-cone–driven, and rod-driven temporal contrast sensitivities (tCSs) in patients with Stargardt disease 1/fundus flavimaculatus (STGD1/FF). METHODS. Fourteen patients (eight male, six female; mean age, 43.21 ± 13.18 years) with genetically confirmed STGD1/FF participated in this study. A dedicated light-emitting diode stimulator was used to measure perifoveal tCSs in an annular test field (1°–6° of visual eccentricity) at temporal frequencies between 1 and 20 Hz. Photoreceptor classes were isolated with the triple silent substitution technique. To compare functional damage among photoreceptor classes, sensitivity deviations (decibels) were calculated based on age-related normal values and then averaged across those frequencies where perception is mediated by the same post-receptoral pathway (L-cone red–green opponent pathway: 1, 2, 4 Hz; luminance pathway: 12, 16, 20 Hz; S-cone pathway: 1, 2, 4 Hz; fast rod pathway: 8, 10, 12 Hz). Sensitivity deviations were compared with infrared scanning laser ophthalmoscopy (IR-SLO) and standard automated perimetry (SAP). RESULTS. Photoreceptor-driven tCSs were generally lower in patients with STGD1/FF than in normal subjects but were without systematic differences among photoreceptors. Although sensitivity deviations were significantly correlated between each other, only luminance-driven L-cone sensitivity deviations were significantly correlated with the IR-SLO area of hyporeflectance (AoH) and SAP central mean deviation within 6° eccentricity (MD6deg). CONCLUSIONS. No systematic differences between photoreceptor classes were detected; however, our data suggest that temporal contrasts detected by the luminance pathway were closely correlated with other clinical parameters (AoH and MD6deg) and might be most useful as functional biomarkers in clinical trials.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Fundus flavimaculatus; Perifovea; Photoreceptors; Stargardt disease; Temporal contrast sensitivity

Photoreceptor-specific loss of perifoveal temporal contrassensitivity in retinitis pigmentosa - Huchzermeyer, Cord; Fars, Julien; Kremers, Jan (Translational Vision Science & Technology, 2020)
Purpose: Inherited retinal diseases affect the L-, M-, S-cones and rods in distinct ways, which calls for new methods that enable quantification of photoreceptor-specific functions. We tested the feasibility of using the silent substitution paradigm to estimate photoreceptor-driven temporal contrast sensitivity (tCS) functions in patients with retinitis pigmentosa. Methods: The silent substitution paradigm is based on substitution of lights of different spectral composition; this offers considerable advantage over other stimulation techniques. We used a four-primary LED stimulator to create perifoveal annular stimuli (2° inner, 12° outer diameters) and used a triple silent substitution to probe photoreceptor-selective tCS. Measurements were performed in a heterogeneous cohort of 15 patients with retinitis pigmentosa and related to those in a control group of nine color-normal healthy observers. Age differences between groups were addressed with a model of age-related normal contrast sensitivity derived from measurements in 20 healthy observers aged between 23 and 83 years. Results: The age-related loss of tCS amounted to 0.1 dB/year in healthy subjects across all photoreceptor subtypes. In patients, tCS was decreased for every photoreceptor subtype; however, S-cone-and rod-driven sensitivities were most strongly affected. Postreceptoral mechanisms were not affected. Conclusions: This feasibility study provides evidence that the silent substitution technique enables the estimation of photoreceptor-selective tCS functions and can serve as an accurate biomarker of photoreceptor-specific contrast sensitivity loss in patients with retinitis pigmentosa. Translational Relevance: We aim to develop tests of visual function for clinical trials of novel therapies for inherited retinal diseases from methods that can currently be used only in vision research labs.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Contrast sensitivity; Photoreceptors; Retinal dystrophy; Retinitis pigmentosa; Temporal vision

Photoreceptor-Specific Temporal Contrast Sensitivities in RP1L1-Associated Occult Macular Dystrophy - Huchzermeyer, Cord; Fars, Julien; Kremers, Jan; Kühlewein, Laura; Kempf, Melanie; Ott, Saskia; Stingl, Krunoslav; Stingl, Katarina (Investigative Ophthalmology & Visual Science, 2023)
Purpose: The purpose of this study was to compare L-, M-, S-cone-, and rod-driven temporal contrast sensitivities (tCS) in patients with RP1L1-associated autosomal-dominant occult macular dystrophy (OMD), and to investigate how photoreceptor degeneration determines which post-receptoral channels dominate perception. Methods: Photoreceptor isolating stimuli were created with the silent substitution technique. Photoreceptor-selective tCS deviations (D L-cone/M-cone/S-cone/Rod) were obtained as a function of temporal frequency with identical retinal adaptation, by subtracting tCS from age-corrected normal values. A linear-mixed effects model was used for analysis. Results: Eleven genetically confirmed patients were included (7 women, 5 men; age = 52.27 ± 14.44 years). Overall, L- and M-cone-driven sensitivity deviations (DL-cone and DM-cone) were more negative than DS-cone; DRod was normal at frequencies between 8 and 12 Hz in all subjects. Rod-driven tCS functions allowed identification of two subgroups of patients: one with band-pass properties and one with low-pass properties, suggesting dominance of different post-receptoral filters. The same filtering properties were observed in L-cone-driven tCS functions. Furthermore, the two subgroups also differed in clinical parameters (spherical equivalent, BCVA, perimetry, and ocular coherence tomography (OCT) reflectivity of the ellipsoid zone relative to the RPE). Conclusions: OMD was characterized predominantly by deterioration of L- and M-cone-cone driven function in the perifovea. Rod-driven functions were normal. Differences in the photoreceptor signals were further modified by postreceptoral filters.
CRIS-Team Scopus Importer:2023-07-07

Psychometric curves in retinitis pigmentosa patients - Fars, Julien; Huchzermeyer, Cord; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-10-01

Relationship between temporal L-coneflicker sensitivity and established clinical parameters in Stargardt's disease - Huchzermeyer, Cord; Fars, Julien; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-10-15

Serum levels of olanzapine are associated with acute cognitive effects in bipolar disorder - Shoshina, Irina I.; Almeida, Natalia L.; Oliveira, Milena E.C.; Trombetta, Bianca N.T.; Silva, Gabriella M.; Fars, Julien; Santos, Natanael A.; Fernandes, Thiago P. (Psychiatry Research, 2022)
Bipolar (BPD) patients have deficits in cognition, but there are still controversies about the effects of some medications on their cognitive performance. Here, we investigated the relationship between cognition in terms of executive functions, memory, and attention in both first-episode medication-naive BPD patients and BPD patients taking olanzapine. Forty-one healthy controls, 40 unmedicated drug-naive BPD patients, and 34 BPD patients who took only olanzapine were recruited for the study. Cognitive performance was assessed using the Flanker test, Stroop test, and Corsi-block test. Bayesian multivariate regression analysis was run considering maximum robustness to avoid bias and to predict the outcomes. Our results revealed that unmedicated medication-naive BPD patients performed worse than healthy controls and the olanzapine group in some tasks. Additionally, BPD patients who took olanzapine had better cognitive performance than healthy controls and unmedicated BPD patients. The acute cognitive effects were predicted by olanzapine dosage and serum levels (i.e., large effects). The potential pro-cognitive effects of olanzapine in BPD patients should be carefully interpreted by considering various other clinical variables. We expect that our findings will contribute to further research in this area, with the goal of helping other researchers, patients, and the population.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Bipolar disorder; Cognition; Cognitive tests; Medication; Olanzapine; Serum levels